2007
DOI: 10.1055/s-2006-927399
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomelanome der Aderhaut

Abstract: Age-related macula degeneration (AMD) is the cause for one third of all pseudomelanomas. Because of its increasing incidence in the future, more attention must be paid to AMD in the differential diagnosis of chorioretinal lesions suspicious of melanoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 12 publications
0
1
0
2
Order By: Relevance
“…In a retrospective analysis of 12,000 patients referred for choroidal melanoma, the frequency of pseudomelanoma was reported as 14.4% by Shields et al [ 2 ]. Another study revealed a pseudomelanoma frequency of 53.7% (246/458) among eyes examined for choroidal melanoma [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective analysis of 12,000 patients referred for choroidal melanoma, the frequency of pseudomelanoma was reported as 14.4% by Shields et al [ 2 ]. Another study revealed a pseudomelanoma frequency of 53.7% (246/458) among eyes examined for choroidal melanoma [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Im Zeitverlauf zeigt die hämorrhagische Pigmentepithelabhebung eine langsame Verkleinerung und bestätigt damit die Diagnose PEHCR im Gegensatz zum malignen Aderhautmelanom. Bei Erstvorstellung des Patienten kann diese Differenzialdiagnose jedoch schwierig sein [5]. Unsere Fallbeschreibung zeigt die typischen Befunde einer PEHCR und die Abgrenzung zum malignen Melanom der Aderhaut.…”
Section: Hintergrundunclassified
“…"Pseudomelanomen" gezählt werden kann [7]. Zu der Gruppe der Pseudomelanome gehören unter anderem: disciforme (pseudotumoröse) altersbedingte Makuladegeneration, Hypertrophie des retinalen Pigmentepithels (RPE), Melanozytom, Aderhauthämangiom und -metastase sowie subretinale Blutung bei Makroaneurysma [9]. Für die Abklärung bzgl.…”
Section: Diskussion !unclassified